2020
DOI: 10.1007/978-3-030-50621-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Druggable Sphingolipid Pathways: Experimental Models and Clinical Opportunities

Abstract: Intensive research in the field of sphingolipids has revealed diverse roles in cell biological responses and human health and disease. This immense molecular family is primarily represented by the bioactive molecules ceramide, sphingosine, and sphingosine 1-phosphate (S1P). The flux of sphingolipid metabolism at both the subcellular and extracellular levels provides multiple opportunities for pharmacological intervention. The caveat is that perturbation of any single node of this highly regulated flux may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 432 publications
(294 reference statements)
0
3
0
Order By: Relevance
“…230 SPHK modulators, S1PL modulators, and S1P scavengers have attracted much attention. 231 Using transgenic animals expressing fluorescently labeled S1PRs, SPHKs, and other sphingolipid-metabolic enzymes, the mechanism regulating these enzyme-receptor systems in vivo can be identified and utilized as a tool for future research. Nevertheless, these bioactive sphingolipid metabolites are rapidly transformed into each other and are intermediates in complex sphingolipid biosynthesis.…”
Section: Prospects and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…230 SPHK modulators, S1PL modulators, and S1P scavengers have attracted much attention. 231 Using transgenic animals expressing fluorescently labeled S1PRs, SPHKs, and other sphingolipid-metabolic enzymes, the mechanism regulating these enzyme-receptor systems in vivo can be identified and utilized as a tool for future research. Nevertheless, these bioactive sphingolipid metabolites are rapidly transformed into each other and are intermediates in complex sphingolipid biosynthesis.…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…Studies have shown that the diverse biological effects of S1P mainly depend on the subtype of adaptor proteins and the specific expression of GPCRs in tissues 230 . SPHK modulators, S1PL modulators, and S1P scavengers have attracted much attention 231 . Using transgenic animals expressing fluorescently labeled S1PRs, SPHKs, and other sphingolipid‐metabolic enzymes, the mechanism regulating these enzyme‐receptor systems in vivo can be identified and utilized as a tool for future research.…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…In blood, S1P exists as a complex with its protein carrier chaperones that include albumin, apolipoprotein M (ApoM), and ApoA4, which presents S1P to its cognate receptors (Blaho, 2020).…”
Section: Tcn2 Functions As a Sphingosine And Fty720 Chaperone Promoting Cd320 Signalingmentioning
confidence: 99%